“Bodily Difference” as a Category of Historical Analysis - Kolářová, Kateřina; Storchová, Lucie (Dějiny – teorie – kritika, 2011)
The collection of texts that we present in this special section introduces disability and bodily difference as a category of historical analysis. In the editorial we argue against the so-called minoritising view of disability and for an approach that discloses disability as a material effect of power/knowledge system and historical processes of normalisation. The presented texts were originally read at a conference Representation of bodily difference through interdisciplinary perspective (October 6-7th, 2010). It was its aim to discuss the analytical potential of “disability” and to instigate interest in disability-based historical analysis and research. The students and junior researchers oriented event was followed by an international conference Cripping Neoliberalism: Interdisciplinary Perspectives on Governing and Imagining Dis/Ability and Bodily Difference (October 8-9th, 2010), both of the event were organized with the support of School of Humanities, Charles University and the Institute of Philosophy of the Academy of Sciences of the Czech Republic.